Dampak Pertumbuhan Ekonomi, Kemiskinan, Pengangguran, dan Belanja Daerah terhadap Indeks Pembangunan Manusia di Nusa Tenggara Timur tahun 2013-2023 - Hera, Maria Helena Gani Doren; Asmara, Kiky (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This research aims to examine the impact of economic growth, poverty, unemployment and regional spending on the HDI or human development index in the East Nusa Tenggara region during the period 2013 to 2023. The methodology used is multiple linear celebration analysis by applying secondary data as obtained through DJPK and BPS. This research shows that the results of economic growth and unemployment have no influence on the HDI in NTT, while the poverty variable is found to have a negative influence on the HDI, indicating that high levels of poverty contribute to the low quality of human development. Meanwhile, regional spending has a positive impact on HDI, showing that increasing the use of regional spending is able to support improvements in the quality of life of the community.